Experimental and theoretical analyses of ZnO nanoparticles deposited onto single-wall carbon nanotubes. Issue 8 (2nd August 2016) - Galvan, D. H.; Alonso, G.; Tejeda, M.; Torres, A.; Reeja-Jayan, B.; Ferrer, D.; Posada-Amarillas, A.; Barraza-Jimenez, D.; José-Yacamán, M.
ABSTRACT: Experimental and theoretical studies were performed on Single Wall Carbon Nanotubes (SWCN) decorated with ZnO nanoparticles located on the surface of the SWCN. Measurements of High Resolution Transmission Electron Microscopy (HRTEM) and Photoluminescence were performed, and theoretical calculations were carried out under the Extended Hückel Tight Binding Approximation. HRTEM results provide information about the existence of SWCN with ZnO nanoparticles on top. A considerably enhancement in the Photoluminescence (PL) behavior of the hybrid system was obtained as compared to pristine SWCN. Calculated energy bands of the pristine SWCN provide an energy gap of 0.06 eV. When the ZnO cluster is located onto the SWCN the new system behaves as a metal. Analysis of total and Partial Density of States (PDOS) provides information about each atom orbital contribution to the total DOS. It is shown that carbon contributes with p-orbitals while Zn contributes with p- and a very small contribution of d-orbitals. The overlap of all these contributions produces hybridized orbitals, which may likely be responsible for the enhancement of Photoluminescence on the new hybrid system.